CUM SE CONSTRUIEȘTE IDENTITATEA UNEI BIBLIOTECI - GHIURCO, președinte al Filialei Iași a Asociației Naționale a Bibliotecarilor și Bibliotecilor Publice din România, Bogdan (BIBLIOPOLIS, 2020)
When you hear - the library - the first association is the book. After, in function of personal experience you can think about a dusty place, an annoyed librarian or the librarian that helped you in childhood to do home works. However, the brand is more than book and librarian. The brand is the totality of Information captured and interpreted by the potential user in contact with the institution and our services. The institution’s brand is always connect to the image. It is etymologically, the sensation (perception, feeling) etched on the customer memory about the institution or our services. The author demonstrates, by examples of international and national practice this assumption from the association with the book, vision, mission, then detecting the brand elements, functions, logo and slogan, suggesting how must not to be a logo and slogan.